Metformin impairs trophoblast metabolism and differentiation in a dose-dependent manner - Nashif, Sereen K.; Mahr, Renee M.; Jena, Snehalata; Jo, Seokwon; Nelson, Alisa B.; Sadowski, Danielle; Crawford, Peter A.; Puchalska, Patrycja; Alejandro, Emilyn U.; Gearhart, Micah D.; Wernimont, Sarah A. (Frontiers in Cell and Developmental Biology, 2023)
Metformin is a widely prescribed medication whose mechanism of action is not completely defined and whose role in gestational diabetes management remains controversial. In addition to increasing the risk of fetal growth abnormalities and preeclampsia, gestational diabetes is associated with abnormalities in placental development including impairments in trophoblast differentiation. Given that metformin impacts cellular differentiation events in other systems, we assessed metformin’s impact on trophoblast metabolism and differentiation. Using established cell culture models of trophoblast differentiation, oxygen consumption rates and relative metabolite abundance were determined following 200 µM (therapeutic range) and 2000 µM (supra-therapeutic range) metformin treatment using Seahorse and mass-spectrometry approaches. While no differences in oxygen consumption rates or relative metabolite abundance were detected between vehicle and 200 µM metformin-treated cells, 2000 µM metformin impaired oxidative metabolism and increased the abundance of lactate and TCA cycle intermediates, α-ketoglutarate, succinate, and malate. Examining differentiation, treatment with 2000 µM, but not 200 µM metformin, impaired HCG production and expression of multiple trophoblast differentiation markers. Overall, this work suggests that supra-therapeutic concentrations of metformin impair trophoblast metabolism and differentiation whereas metformin concentrations in the therapeutic range do not strongly impact these processes.